FLEXURAL CAPACITY ASSESSMENT OF BRICK AGGREGATED PRE-CRACKED RC BEAM STRENGTHENED WITH CARBON FIBER POLYMER (Malaysian Journal of Civil Engineering, 2019)
Ageing and improvements to design code has led to many existing RC structures made of locally available brick aggregates are now found structurally deficient and are in need of rehabilitation. This research emphases on flexural capacity assessment and investigation of failure modes of Carbon Fiber Reinforced Polymers (CFRP) strengthened brick aggregated RC beams. Flexural performance of the RC beam specimens are evaluated using four point bending method. Six RC beams (initially cracked) with CFRP strengthening were tested by varying (i) type of CFRP, (ii) reinforcing area, (iii) anchorage type; and (iv) number of CFRP layers. Two beams were tested as control specimens. Unidirectional carbon fiber sheet (Tow Sheet) and individually hardened continuous fiber strands woven into sheet form (Strand Sheet) were used. Simple flexure failure was obtained for unstrengthened RC beams while end plate and interfacial debonding were observed for the initially cracked CFRP strengthened RC beams. Strengthening of pre-cracked beams using Strand Sheet gave better performance compared to Tow sheet. Overall flexural strength improvement of CFRP strengthened beams varied from 12% to 34% with respect to unstrengthened beams depending on strengthening methods.